A multicenter study evaluation of the ClearLLab 10C panels. Issue 2 (15th July 2020) - Hedley, Benjamin D.; Cheng, Guoyan; Keeney, Michael; Kern, Wolfgang; Padurean, Adrian; Luider, Joanne; Chin‐Yee, Ian; Lowes, Lori E.; Rohrbach, Justin; Ortega, Robert; Smit, Astrid; Lo, Ka‐Wai; et al.
Abstract: Multiparameter flow cytometry plays an important role in the diagnosis, staging, and monitoring of patients with a suspected hematological malignancy. The ClearLLab 10C Panels consist of four reagent panels (B‐Lineage Tube, T‐Lineage Tube, and 2 Myeloid Lineage Tubes), each consisting of 10 color/10 antibody conjugates utilizing Beckman Coulters proprietary dry format optimized for investigating patients with suspected leukemia or lymphoma. A multicenter study was conducted to evaluate the performance of the ClearLLab 10C Panels for qualitative assessment of normal versus abnormal phenotype in peripheral blood, bone marrow, and lymph node samples with suspected hematological malignancies. ClearLLab 10C was compared to laboratory developed tests (LDTs) and final clinical diagnosis. Four clinical sites were used to enroll patient's spent specimens ( n = 453); three laboratories in North America and one in Europe. Of the 453 specimens, 198 had no malignancy and 255 contained an abnormal population. The diagnostic accuracy of the ClearLLab 10C Panels was achieved with sensitivity of 96% and specificity of 95% with respect to patient final clinical diagnosis. The agreement of phenotyping between ClearLLab10C Panels and LDTs was 98%. Any differences noted between ClearLLab 10C and LDT were due to either the presence of populations below the level of detection, the lack of clinical information provided to the evaluators, or marker(s) not present in these panels. Overall, the ClearLLab 10C demonstrated excellent agreement to LDTs and diagnosis. These four reagent panels can be adopted by individual laboratories to assess the presence or absence of malignancy.